c - 9 (b, 1997)
Author's memoirs of 1975 political conspiracy in Bangladesh and assassination of Sheikh Mujibur Rahman, 1922-1975, first president of Bangladesh.
In Bengali.
Keywords: Mujibur Rahman, -- Sheikh, -- 1920-1975 -- Assassination; Bangladesh -- Politics and government -- 1971.